Peran Keluarga Sebagai Sumber Pendidikan Karakter Untuk Membentuk Kepribadian Anak Dalam Berfikir - Adelia Nur Azzani; St. Alikha Allyasari (BADAN PENERBIT STIEPARI PRESS, 2023)
So we can simplify that the smallest unit of a teenager's growth comes from the family, because after all the family is the main pillar of success in the growth of a small child to become an obedient teenager. The family will shape a person's character and influence his environment because the family is the first and foremost environment for character formation. Because it is education in the family that the child's character is first formed so that before he is sent to school he already has his own knowledge and character from his home. Character education itself can be interpreted as a process of providing guidance to students to develop attitudes and behavior optimally. From the results of the field analysis it is determined that parents are the main characters for a child so that they can understand the importance of character education and how to apply good character traits, of course by educating parents at home because children are a picture of their parents, if the example of If the parents are good, then the child will definitely learn to be the character that has been exemplified by his parents. The good or bad character of the child is greatly influenced by the family environment. The process of character education for children in the family can be carried out by parents using several methods including exemplary, habituation, advice and punishment as well as motivation for children. The achievement of the character education process in the family environment depends on harmony between parents, children, the methods used and the environment that supports the educational process.